A nearby transiting rocky exoplanet that is suitable for atmospheric investigation - Trifonov, Trifon; Caballero, J. A.; Morales, J. C.; Seifahrt, A.; Ribas, I.; Reiners, A.; Bean, J. L.; Luque, R.; Parviainen, H.; Pallé, E.; Stock, Stephan; Zechmeister, M.; et al. (Science, 2021)
A transiting rocky planet 8 parsecs away - Most exoplanets have been detected using either the radial velocity (RV) method or the transit method, which provide only limited information on the planet's physical properties. In the rare cases in which both methods detect the same planet, the combination determines the planet's mass, radius, and density. Trifonov et al. identified a planet, Gliese 486 b, using both RV and transit data. The host star is a red dwarf only 8 parsecs away, making this one of the closest exoplanet systems known. A rocky super-Earth, Gliese 486 b has an equilibrium surface temperature of 700 kelvin. The authors say that it is observationally favorable for searches for an atmosphere. - Science, this issue p. 1038 - Spectroscopy of transiting exoplanets can be used to investigate their atmospheric properties and habitability. Combining radial velocity (RV) and transit data provides additional information on exoplanet physical properties. We detect a transiting rocky planet with an orbital period of 1.467 days around the nearby red dwarf star Gliese 486. The planet Gliese 486 b is 2.81 Earth masses and 1.31 Earth radii, with uncertainties of 5%, as determined from RV data and photometric light curves. The host star is at a distance of ~8.1 parsecs, has a J-band magnitude of ~7.2, and is observable from both hemispheres of Earth. On the basis of these properties and the planet’s short orbital period and high equilibrium temperature, we show that this terrestrial planet is suitable for emission and transit spectroscopy. - A hot rocky super-Earth exoplanet orbits a red dwarf star only 8 parsecs away. - A hot rocky super-Earth exoplanet orbits a red dwarf star only 8 parsecs away.